OPTIMASI MANAJEMEN JARINGAN NIRKABEL DENGAN CAPSMAN DI MIKROTIK ROUTEROS - Sakti, Ferdian; Mufarrihah , Iftitaahul (Inovate, 2025)
Efficient and centralized management of wireless networks is a primary requirement in modern network infrastructure, especially in large-scale organizations. MikroTik RouterOS provides a Controlled Access Point System Manager (CAPsMAN) feature that enables centralization of wireless access point settings, thereby reducing the complexity of individual device management. This research aims to optimize wireless network management using CAPsMAN on MikroTik RouterOS. Research methods include network requirements analysis, device configuration, CAPsMAN implementation, and network performance evaluation based on throughput, latency and connection stability parameters. The results show that the use of CAPsMAN significantly improves network management efficiency by making it easier to set network parameters such as SSID, security, and bandwidth allocation. Additionally, this implementation reduces configuration time by up to 40% compared to manual methods. Testing also showed network stability improvements of up to 20% in an environment with 35 access points. This research provides a practical contribution in utilizing CAPsMAN features to improve the management of complex wireless networks. This implementation is especially relevant for educational institutions, companies, and other work environments that require a reliable and easy-to-manage network infrastructure. It is hoped that this research will become a reference for network administrators in adopting similar technology to face the challenges in managing wireless networks that continue to develop. Keywords: CAPsMAN, MikroTik RouterOS, Network throughput, Network latency